Pendampingan Branding serta Promosi Offline dan Digital UMKM Desa - Mohamad Ma'mun; M. Malfin Zainal Asyiqin Malfin; Rizka Rahma Wati Rahma; Trisfirdaona Rashamida Iqdam Ona; Andri Wicaksono Andri (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
Empowering Micro, Small, and Medium Enterprises (MSMEs) is a strategic step in sustainably improving the village economy. This article discusses a training program titled "Branding Assistance and Offline and Digital Promotion of MSMEs in Mejono Village," held in Mejono Village, Kediri Regency. This activity aims to improve the understanding and skills of MSMEs in building brand identities and marketing products through social media and digital platforms such as marketplaces. The methods used included educational counseling, interactive discussions, and technical demonstrations on how to sell on Shopee and Facebook, from creating accounts, taking product photos, writing descriptions, to determining selling prices. This activity presented competent speakers in the fields of digital marketing and e-commerce, and involved local MSMEs as the main participants. The results of the activity showed an increase in participants' awareness of the importance of branding in differentiating products, as well as how digital promotion can expand market reach without the need for a physical store. Participants also gained an initial understanding of digital marketing communications based on the Attention, Interest, Desire, and Action approach (AIDA). This program is expected to be an inspiration for other villages in developing the potential of Micro, Small, and Medium Enterprises through the use of digital technology.